Ökumenisches Kirchenrecht im Zerrbild historiographischer Erzählung: Die mediterrane Zölibatsdiskussion rund um das Concilium Quinisextum ( 691/692? ) und ihr kakophoner Nachhall in lateinischen Geschichtswerken des frühen Mittelalters - Esders, Stefan (Frühmittelalterliche Studien, 2024)
The Quinisext Council, assembled in Constantinople shortly after 690 to issue a series of more than 100 canons on practical issues and on clerical discipline, was designed as an Ecumenical council, but failed to gain ‘universal’ acceptance in the West. Moving beyond traditional interpretations which saw the conflict over the Quinisext Council largely as one between Emperor Justinian II in Constantinople and the papacy in Rome, the article asks how issues related to the Quinisext Council were received in the churches of the Exarchate of Ravenna and the Lombard, Visigothic, Frankish and Anglo-Saxon kingdoms. Drawing on accounts in Paulus Diaconus’ ‘History of the Lombards’, the ‘Chronicle of Alfons III’ (of Asturia) and Agnellus’ ‘Book of Pontiffs of the Church of Ravenna’, it is argued that there must have been a much wider debate about the Quinisext canons on celibacy and on chastity of clerics. As is shown by the analysis of these sources, some of the Quinisext canons on these topics were accepted in the exarchate of Ravenna, the Lombard kingdom of Italy and the Visigothic kingdom in Spain and Southern Gaul around 700; only when attitudes changed profoundly after the mid-eighth century, the acceptance of the council’s decisions by rulers and bishops became subject to polemical narratives in later historiography. By contrast, a case can be made on the basis of synodal decisions, canon law, hagiographical texts, theological treatises and chronicles that in the Frankish and Anglo-Saxon kingdoms, the Quinisext canons on clerical marriage were refuted by bishops, who confirmed older positions on the debated issues as transmitted through canon law tradition. Asking what may have caused both the acceptance and rejection of the Council’s decisions and revisiting the development of the papacy’s attitude to the Quinisext canons, it is argued here that juxtapositions and a priori-statements on religious culture in ‘East’ and ‘West’ are not helpful to understand the wide-ranging connectivity and communication that becomes visible from this debate. A Mediterranean perspective that fully embraces the world of the post-Roman ‘West’ including Britain does more justice to the openness of historical processes around 700.